Tungsten–platinum μ-carbido and μ-methylidyne complexes. Issue 82 (30th September 2019) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : The lithiocarbyne [W]CLi ([W] = W(CO)2 (Tp*); Tp* = tris(dimethylpyrazolyl)borate) with divalent platinum complexes afford access to μ-carbido, μ-methylidyne and carbyne-based metallo-ligand complexes. Abstract : Reactions of the lithiocarbyne [W]CLi ([W] = W(CO)2 (Tp*); Tp* = tris(dimethylpyrazolyl)borate) with divalent platinum complexes [PtCl(terpy)]PF6, [PtCl2 (η-C4 R4 )] (R = Me, Et), and [PtCl2 (phen)] afford access to μ-carbido, μ-methylidyne and carbyne-based metallo-ligand complexes [Pt(C[W])(terpy)]PF6, [Pt(μ-HC[W])2 ] and [Pt(C[W])Cl(phen-C[W]-2)], respectively, the last of which provides a rare example of intermolecular organometallic nucleophilic attack at coordinated phenanthroline.